Community Based Evaluation of Malaria Rapid Diagnostic Test (ICT) Comparing with Conventional Method of Microscopy (Medical Forum Monthly, 2024)
Objective: to estimate the validity of immunochromato graphic test (ICT) while comparing it with the conventional method of microscopy.Study Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the Community Medicine, Liaquat College of Medicine & Dentistry, Karachi from July 2015 to November 2015.Materials and Methods: A sample of 296 community members of both sexes and above one year age was taken who were diagnosed clinically as a suspected case of malaria through Community based surveillance in katchi abadi, Karachi. Selected subjects were interviewed using a structured and pre-tested questionnaire regarding socio-demographic variables, their symptoms of malaria. A venous blood sample by the standard venipuncture procedure was collected was from each subject and blood CP, ICT and microscopy was performed for Plasmodium Falciparum or Plasmodium Vivax malaria diagnosis and confirmation of the parasite. Data was analyzed on SPSS version 20. The validity of each test was calculated by OpenEpi software.Results: Using a Wilson score method, the sensitivity of ICT was 82.14% and specificity was 97.01%. The Positive Predictive Value (PPV) for ICT was 74.19% whilst the Negative Predictive Value (NPV) was 98.11%.Conclusion: Compared with the results of the direct microscopy, ICT gave almost perfect agreement and near-perfect sensitivities and specificities in the detection of the clinically most important species of Plasmodium.